Is Weak Acid Beneficial for Addressing Checkpoint Inhibitor–Triggered Cancer Hyper Progression in Anti-PD1/PD-L1 Immunotherapies? - Yulin Wan MS; Shanshan An MS; Yanchao Zhou MS; Jiaming Zhang MS; Ying Zhang MS; Tao Gan PhD; Qiuyun Liu PhD (Cancer Control, 2020)
Numerous cases of checkpoint inhibitor–triggered cancer hyperprogression have been documented. A previous hypothesis attributes cancer onset to the local buildup of hydrogen chloride, jointly mediated by hydrogen bond donors and acceptors and basic amino acids. The anti-PD1/PD-L1 immunotherapies may have caused a surge of protons or chloride ions for the effective treatment of neoplasm, thus giving rise to the local formation of hydrogen chloride and subsequently cancer hyperprogression in some susceptible individuals. It was postulated that the local strength of acidity is critical for tumor growth and metastasis, as the intake of weak organic acids reduces cancer risks. The anti-PD1/PD-L1 immunotherapies can be integrated with weak organic acids to reduce adverse reactions and generate better anticancer outcomes.